Perkembangan Dan Ukuran Pertama Kali Matang Gonad (Lm50) Ikan Lemadang (Coryphaena hippurus Linnaeus, 1758) Betina Di Perairan Selatan Bali - Hety Hartaty; Iriani Setyawati; FX. Sudaryanto (Metamorfosa: Journal of Biological Sciences, 2021)
Research on the reproductive biology of fish can provide information on spawning frequency, spawning success, spawning time, and size at first maturity. This research aimed to determine the reproductive biology of common dolphinfish (Coryphaena hippurus Linnaeus, 1758) landed at the fish landing site (PPI) Kedonganan, Badung, Bali. Sampling was conducted in May - September 2018. A total of 42 female common dolphinfish with length ranged between 41-110 cm FL were obtained from hand-line fishery based on FADs. Ovaries were prepared using the paraffin method and Harris Haematoxylin-Eosin staining for histological observation. The results showed that the gonad maturity level in adult females was: spawning (38.10%), spawning capable (35.71%), regressing-potentially reproductive (4.76%), regressed 1 (2.38%), regressed 2 (2.38%), and regenerating (2.38%). Immature female: immature (9.52%) and developing (4.76%). Oocyte diameter ranged between 43,20 – 864,66 µm with an average of 430,99 µm. Fecundity in fish size 49-75 cm FL ranged from 30,720-433,080 eggs / fish with an average of 129,594 eggs / fish. The difference in the level of oocytes in the ovaries at the same time showed that female common dolphinfish in the southern Bali waters has an asynchronous ovary development and indeterminant fecundity with multiple spawning strategies and size at first maturity (Lm50) was 43.2 cm FL. Keywords: common dolphinfish, gonad histology, size at maturity